Anatomy of the Breast Fascial System: A Systematic Review of the Literature. Issue 1 (January 2022) - Duncan, Anna M.; Al Youha, Sarah; Joukhadar, Nadim; Konder, Ricarda; Stecco, Carla; Wheelock, Margaret E.
Abstract : Background: Understanding the anatomy of the fascial and ligamentous structures of the breast is important in both aesthetic and reconstructive breast surgery. Several structures have been identified that play a significant role in the aesthetic qualities and support of the breast warranting consideration in the context of breast reconstruction. Methods: The authors performed a systematic review of anatomical, clinical, histologic, and radiologic studies that have described, characterized, and named these structures. The authors have summarized and critically appraised prior research to clarify and define the key fascial structures of the breast, their anatomical function, and their clinical significance in aesthetic and reconstructive breast surgery. Results: Through their review, six distinct breast fascial structures were encountered consistently in the literature. The authors have organized them into intraglandular and extraglandular structures and have reviewed their significance in the context of reconstructive breast surgery. Conclusions: The primary fascial structures of the breast are important anatomical landmarks with numerous clinical applications. Cooper ligaments divide the breast parenchyma. The superficial and deep layers of the superficial fascia encase the breast in a "pocket, " condensing into one thickened layer of fascia along the peripheral breast footprint. The inframammary fold supports and defines the inferior pole. The horizontal septum is a reliable neurovascular landmark. The vertical septum is a newly discovered fascial structure. There are certainly clinical implications that have yet to be described because of the relatively limited and disputed information on the fascia of the female breast and, ultimately, more research is warranted. Abstract : Supplemental Digital Content is available in the text.